The influence of total knee arthroplasty design on kneeling kinematics: a prospective randomized clinical trial. (1st January 2021) - Lynch, Joseph T.; Perriman, Diana M.; Scarvell, Jennie M.; Pickering, Mark R.; Galvin, Catherine R.; Neeman, Teresa; Smith, Paul N.
Abstract : Aims: Modern total knee arthroplasty (TKA) prostheses are designed to restore near normal kinematics including high flexion. Kneeling is a high flexion, kinematically demanding activity after TKA. The debate about design choice has not yet been informed by six-degrees-of-freedom in vivo kinematics. This prospective randomized clinical trial compared kneeling kinematics in three TKA designs. Methods: In total, 68 patients were randomized to either a posterior stabilized (PS-FB), cruciate-retaining (CR-FB), or rotating platform (CR-RP) design. Of these patients, 64 completed a minimum one year follow-up. Patients completed full-flexion kneeling while being imaged using single-plane fluoroscopy. Kinematics were calculated by registering the 3D implant models onto 2D-dynamic fluoroscopic images and exported for analysis. Results: CR-FB designs had significantly lower maximal flexion (mean 116° (SD 2.1°)) compared to CR-RP (123° (SD 1.6°)) and PS-FB (125° (SD 2.1°)). The PS-FB design displayed a more posteriorly positioned femur throughout flexion. Furthermore, the CR-RP femur was more externally rotated throughout kneeling. Finally, individual patient kinematics showed high degrees of variability within all designs. Conclusion: The increased maximal flexion found in the PS-FB and CR-RP designs were likely achieved in different ways. The PS-FB design uses a cam-post to hold the femur more posteriorly preventing posterior impingement. The external rotation within the CR-RP design was surprising and hasn't previously been reported. It is likely due to the polyethylene bearing being decoupled from flexion. The findings of this study provide insights into the function of different knee arthroplasty designs in the context during deep kneeling and provide clinicians with a more kinematically informed choice for implant selection and may allow improved management of patients' functional expectations. Cite this article: Bone Joint J 2021;103-B(1):105–112.